A Study of Some Growth of Two Hyborids of Tomato Plant (Lycopersicon Esculentum Mill.) Grown Under The Influence of Sodium Chloride in The Nutrient Solution and Proline Spraying to Shoot. - Al-Saedi, A.J.H.; Al-Hattab, Z.M.SH. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment was conducted inside a glasshouse at the Department of Biology/ Education college Ibn- Alhaitham/ Baghdad University during the growing season 2010-2011. The aim of the study was to assess the influence of increasing of NaCl concentration in the nutrient solution and different concentrations of proline as spray on the vegetative growth on the chlorophyll content, soluble carbohydrates percentage, flowers number and the proline content of vegetative growth. The aim of this study was also to determine the satiable concentration of proline while decrease the injerion. Effect of NaCl on the studied traits of two hyborids of tomato plants namely Olga F1 and Hymar F1. Sodium chloride concentration of 0, 100. 150 mM/L and proline with 0, 15, 30 mg/L were used Factorial experiment within Completely Randomized Design (C.R.D.) was used with 3 replicates Cie. 54 Plastic containers were included. Results revealed that, Olga F1 was superior with increase percent 4.95, 58.66, 15.66 and (16.22, 10.82)% for the above mentioned characteristics respectively and for the tow harvests of the last trait. Results also revealed a decrease of the studied characteristics with increasing NaCl concentration from Zero up to 150 mM/L in the nutrient solution giving a decrease percent of 23.87, 32.87 and 37.70% for the its three traits, where as proline concentration increased as NaCl increased to 150mM/L giving 168.30 and 151.48% increment percentage as compared with the control for the two harvests respectively. It coaled be concluded that, increasing the proline to 15 mg/L caused a decrease in the injurious effect of NaCl, and the hybrid Olga F1 was more to tolerant to the salinity than Hymar F1 in all studied traits